PARENTAL PARTICIPATION IN PROVIDING ANTI-CORRUPTION EDUCATION TO CHILDREN AS AN EFFORT TO PREVENT CORRUPTION IN THE CITY OF KUPANG - Friandry Windisany Thoomaszen; Sance Mariana Tameon (Asia Pacific Fraud Journal, 2018)
Corruption is a very complex problem experienced by the Indonesian people. Compared to other provinces, Nusa Tenggara Timur (NTT) Province was the second most corrupt province in Indonesia. Therefore, this study focuses on cases of corruption that occur in Kupang, the capital of NTT province. There are many factors that support the spread of corruption cases in NTT. One of the factors highlighted in this study is the lack of understanding of the community, especially the family, in providing anti-corruption value, which is integrated with Protestant values, to children. The general purpose of this study was to find out the extent of parental participation in providing anti-corruption education to late childhood, as an effort to prevent corruption cases in Kupang. This study used a quantitative approach with descriptive survey research methods. Sampling was done using random sampling techniques. Data analysis was performed using descriptive statistics and cross-tabulation. Research subjects were 103 Protestant parents having children and living in Kupang City. The results show that parents’ understanding of corruption is 93.20%. This means that most parents have a correct and accurate understanding of corruption. However, the parents’ understanding of anti-corruption education is only 53.39%. 67.96% or 70 parents do not understand about nine (9) anti-corruption values, and only 32.03% or 30 parents understand them. Different levels of parents’ education lead to differences in parental activity in providing anti-corruption education, especially in the depth of value and the material.